Clinical description of dementia patients concerned by acetylcholinesterase inhibitor and other drugs in Dr. Soeharto Heerdjan Psychiatry Hospital - Muhammad Fahmi Syah Putra; Nasruddin Noor (Bagian Farmakologi, Fakultas Kedokteran Universitas YARSI, 2020)
Background: Dementia is a syndrome of brain damage caused by cognitive changes due to brain trauma or degenerative, while clinical symptoms in dementia have a variety of both cognitive impairments and non cognitive disorders so that appropriate management in the form of pharmacological interventions is needed.Objective: To determine the clinical symptoms of dementia patients and use of drug Acetylcholinesterase Inhibitor and other drugs as a treatment in the Dr. Suharto Heerdjan Psychiatric Hospital.Methods: Quantitative non-experimental or analytical research, and the determination of samples by consecutive sampling method, that is, all medical records that meet established inclusion and exclusion criteria are included in the study until the number of samples is met.Results: Obtained inclusion criteria of 96 medical records belonging to Dr. Soeharto Heerdjan Psychiatric Hospital patients. with gender of female and male, age presenile dementia (<65 years) and senile dementia (> 65 years) were found. The classification is found in dementia patients including not classified dementia, Alzheimer's dementia, vascular dementia, ytt dementia, parkinson's dementia, and finally dementia ydk, for acetylcholinesterase drugs were founded using donepezil, rivastigmine, and galantamine. The symptoms are obtained with general symptoms of dementia, positive symptoms, and negative symptoms. Comorbid diseases include hypertension, paranoid schizophrenia, residual schizophrenia, tension type headache, anxiety disorders, recurrent depression, and depressive disorders. And other drugs include antipsychotics, antiparkinsonians, mood stabilizers, antidepressants, anxiolytics, anticonvulsants, analgesics, immunosuppressants, antihypertensive agents, vitamins, and N-Methyl-D-Aspartate.Conclusion: Dementia patients at Dr. Soeharto Heerdjan Psychiatric Hospital has the highest diagnosis of Alzheimer's dementia with the most clinical symptoms in sundowner symptoms and delusional symptoms with some of them having the most comorbid disease in the form of hypertension. As for management, drug use in the acetylcholinesterase group in the form of donepezil and other drugs such as antipsychotic drugs in the form of risperidone or olanzapin, and anti-hypertensive drugs in the form of captopril, amlodipine, and beta blockers are drugs that are often used in patients.